2009
DOI: 10.1177/0891243209339913
|View full text |Cite
|
Sign up to set email alerts
|

School Culture and the Well-Being of Same-Sex-Attracted Youth

Abstract: This study assesses how variations in heteronormative culture in high schools affect the well-being of same-sex-attracted youth. The authors focus on the stigmatization of same-sex attraction (rather than identity or behavior) to better understand how heteronormativity may marginalize a wide range of youth. Specifically, the authors use data from the National Longitudinal Study of Adolescent Health to examine how variation across schools in football participation, religious attendance, and urban locale affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 38 publications
(69 reference statements)
0
68
0
5
Order By: Relevance
“…Research on sexual minorities in Anglo-American cultures has shown that their lives have often been defined by social marginalisation (Herek, 2004), living within societies that privilege heterosexuality (Wilkinson and Pearson, 2009). Sexual minorities have also been denied equality under the law (McGhee, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Research on sexual minorities in Anglo-American cultures has shown that their lives have often been defined by social marginalisation (Herek, 2004), living within societies that privilege heterosexuality (Wilkinson and Pearson, 2009). Sexual minorities have also been denied equality under the law (McGhee, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When interpreting this finding, we should keep in mind that the NLLFS adolescents most often reported negative experiences that happened at school. This is not surprising, since classmates play central roles in the lives of developing adolescents (Harris, 1995;Wilkinson & Pearson, 2009). With regard to the school context, Ray and Gregory (2001) found that offspring in lesbianheaded families were bullied more often in elementary school than in high school.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…These studies are a sampling of the myriad survey studies from the last decade that have found correlations between the prevalence of interpersonal discrimination and the negative experiences of LGBTQ youth (Advocates for Children, Inc., 2005;Espelage et al, 2008;Gruber & Fineran, 2008;Morrison & L'Heureux, 2001;Murdock & Bolch, 2005;Poteat et al, 2009;Russell, Seif, & Truong, 2001;Sandfort et al, 2010;Walls et al, 2010;Wilkinson & Pearson, 2009). All of the studies that employ this frame identify the problem facing…”
Section: Onward: Lgbtq Youth As Victimsmentioning
confidence: 99%
“…While most of these survey studies employed quantitative research methods (Birkett, Espelage, & Koenig, 2009;Espelage, Aragon, Birkett, & Koenig, 2008;Gruber & Fineran, 2008;Murdock & Bolch, 2005;Poteat, Espelage, & Koenig, 2009;Sandfort, Bos, Collier, & Metselaar, 2010;Walls, Kane, & Wisneski, 2010;Wilkinson & Pearson, 2009), a few employed qualitative methods (Adelman & Woods, 2006). Prior to 2010, qualitative studies that did not rely on surveys as the primary data source were less prevalent in the field overall, and most focused on the individual experiences or beliefs of educators (Dessel, 2010;McCabe & Rubinson, 2008;Payne & Smith, 2010;Tooms, 2007;Zach, 2010), while a smaller segment of studies focused on the experiences of LGBTQ youth (Davidson, 2009;Lee, 2002;Russell, Muraco, Subramaniam, & Laub, 2009;Savin-Williams, 2005).…”
Section: Sampling Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation